2021
DOI: 10.1038/s41419-021-03605-y
|View full text |Cite
|
Sign up to set email alerts
|

Oleandrin, a cardiac glycoside, induces immunogenic cell death via the PERK/elF2α/ATF4/CHOP pathway in breast cancer

Abstract: Chemotherapeutic agents have been linked to immunogenic cell death (ICD) induction that is capable of augmenting anti-tumor immune surveillance. The cardiac glycoside oleandrin, which inhibits Na+/K+-ATPase pump (NKP), has been shown to suppress breast cancer growth via inducing apoptosis. In the present study, we showed that oleandrin treatment triggered breast cancer cell ICD by inducing calreticulin (CRT) exposure on cell surface and the release of high-mobility group protein B1 (HMGB1), heat shock protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Both PBI-05204 and its active principal ingredient, oleandrin, have been tested in GBM models ( Colapietro et al, 2020a ) and, in addition, have also been shown to be active against a wide number of human tumor cell types such as melanoma ( Lin et al, 2008 ), prostate ( Smith et al, 2001 ), pancreas ( Pan et al, 2015 ), and breast ( Li et al, 2021 ) cancers as well as certain hematologic malignancies. The botanical drug PBI-05204 has gone through both Phase I and II clinical trials in cancer patients and has been shown to be safe as an oral drug for daily administration ( Hong et al, 2014 ; Roth et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both PBI-05204 and its active principal ingredient, oleandrin, have been tested in GBM models ( Colapietro et al, 2020a ) and, in addition, have also been shown to be active against a wide number of human tumor cell types such as melanoma ( Lin et al, 2008 ), prostate ( Smith et al, 2001 ), pancreas ( Pan et al, 2015 ), and breast ( Li et al, 2021 ) cancers as well as certain hematologic malignancies. The botanical drug PBI-05204 has gone through both Phase I and II clinical trials in cancer patients and has been shown to be safe as an oral drug for daily administration ( Hong et al, 2014 ; Roth et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, HMGB1 participates in the regulation of chemo- and radiotherapy resistance in breast cancer 9 , 16 , 17 . Due to the complexity of HMGB1 functions in breast cancer progression, new therapeutic strategies targeting HMGB1 are constantly being developed, such as the identification of potential ICD inducers and the combination therapies with immune checkpoint blockade 18 - 20 .…”
Section: Introductionmentioning
confidence: 99%
“… 55 Also, CRT expression at the membrane was observed after an hour of necroptosis induction. In strong contrast, in apoptotic MCF7 cells, ATP and HMGB1 release peaked only after 12 and 48 hours, respectively, 56 and membrane CRT expression was observed only after 10 hours. Despite these differences, both cell death modalities have been shown to be immunogenic in nature.…”
Section: Hallmarks Of Immunogenic Cell Death (Icd)mentioning
confidence: 74%